Mucosal HIV-1 transmission and prevention strategies in BLT humanized mice - Denton, Paul W. (2012)
Clinical trials testing microbicides and related biomedical interventions to block HIV transmissions have produced contradictory results and to date it is unclear why. Further elucidation of the molecular basis of mucosal HIV transmission and extensive pharmacokinetic and pharmacodynamic analyses are essential to implementing effective prevention strategies. Animal models are of critical importance to this effort and bone marrow-liver-thymus (or BLT) humanized mice have recently emerged as a powerful small animal research platform for in vivo efficacy evaluation of mucosal and parenteral HIV-1 prevention interventions. The availability of this validated system for the pre-clinical evaluation of HIV-1 prevention approaches will accelerate the implementation of the best candidate interventions into clinical trials.